Peptide receptor radionuclide therapy for aggressive pituitary tumors: a monocentric experience. Issue 5 (May 2019) - Giuffrida, G; Ferraù, F; Laudicella, R; Cotta, O R; Messina, E; Granata, F; Angileri, F F; Vento, A; Alibrandi, A; Baldari, S; Cannavò, S
Abstract : In aggressive pituitary tumors (PT) showing local invasion or growth/recurrence despite multimodal conventional treatment, temozolomide (TMZ) is considered a further therapeutic option, while little data are available on peptide receptor radionuclide therapy (PRRT). We analyzed PRRT effectiveness, safety and long-term outcome in three patients with aggressive PT, also reviewing the current literature. Patient #1 (F, giant prolactinoma) received five cycles (total dose 37 GBq) of 111 In-DTPA-octreotide over 23 months, after unsuccessful surgery and long-term dopamine-agonist treatment. Patient #2 (M, giant prolactinoma) underwent two cycles (12.6 GBq) of 177 Lu-DOTATOC after multiple surgeries, radiosurgery and TMZ. In patient #3 (F, non-functioning PT), five cycles (29.8 GBq) of 177 Lu-DOTATOC followed five surgeries, radiotherapy and TMZ. Eleven more cases of PRRT-treated aggressive PT emerged from literature. Patient #1 showed tumor shrinkage and visual/neurological amelioration over 8-year follow-up, while the other PTs continued to grow causing blindness and neuro-cognitive disorders (patient #2) or monolateral amaurosis (patient #3). No adverse effects were reported. Including the patients from literature, 4/13 presented tumor shrinkage and clinical/biochemical improvement after PRRT. Response did not correlate with patients' gender or age, neither with used radionuclide/peptide, but PRRT failure was significantly associated with previous TMZ treatment. Overall, adverse effects occurred only in two patients. PRRT was successful in 1/3 of patients with aggressive PT, and in 4/5 of those not previously treated with TMZ, representing a safe option after unsuccessful multimodal treatment. However, at present, considering the few data, PRRT should be considered only in an experimental setting.